Welcome for thee, but not for me: How demographic parameters and nature experience affect how close to home people accept animals - Fabio S.T. Sweet; Wolfgang W. Weisser (Basic and Applied Ecology)
Animals are a constant presence in urban environments. While there is a handful of studies that have addressed which urban animals people like, there is little knowledge on where in cities people accept animals in relation to their homes. A preceding study by the authors indicated that Munich residents’ preferred proximity to animals is influenced by their attitudes towards these animals. Here, we go a step further and analyse how human demographic parameters and experience with animals influence people’s decision on where to place animals.We used data on demographics, experiences, and attitudes to test how these factors influence how close to their home people accepted different animals – in the form of the closest relational scale chosen for the animals. A multigroup structural equation model with attitudes towards the animals as a mediator and the animals as grouping variables was used to disentangle the effects of different variables for placement, and to compare different animals. Variable selection and path constraint were done using PiecewiseSEM, and final estimates were produced with Lavaan.We found that different demographics and experiences are associated with accepting animals closer to home or further away. People who liked animals more, had higher levels of education, stated that they enjoy spending time in nature more, or help animals in their environment, generally accepted most animals closer to their home. In contrast, people who live in a house instead of an apartment generally wanted most animals further away from home.Our results emphasise that people have a differentiated view of animals that is influenced by both internal and external factors. Taking this into account can help identify reasons for the acceptance or rejection of an animal in urban environments, help guide urban conservation projects, and mediate human-wildlife conflicts.